Counseling in Audiology: Au.D. Students' Perspectives and Experiences - Whicker, John; Muñoz, Karen; Schultz, Jared C. (Seminars in Hearing, 2018)
Counseling in audiology is an important aspect of service delivery. How audiologists interact with patients and foster counseling relationships to help patients and families understand and live with hearing loss can impact outcomes of audiological interventions. Currently, variability exists in how graduate training programs are teaching counseling skills, and the extent to which counseling skills development is supported in clinical experiences is unclear. This article seeks to explore the perspectives related to the importance of counseling and counseling training experiences received through clinical instruction of Au.D. students beginning their final year of study, to identify where counseling training might be limited, and to examine how counseling skills might be better supported. Findings revealed that students generally appreciate the importance of counseling in audiology. Data suggest that how students are supported in developing counseling skills appears to be variable and unstructured.
Keywords: Counseling; audiology; training